Efektivitas Ekstrak Air Rebusan Jarak Cina (Jatropha Multifida) Dan Mahkota Dewa (Phaleria Macrocarpa) Sebagai Larvasida Nyamuk Aedes Aegypti - KHOLIL, Munawar; , Triastuti Rahayu, S.Si, M.Si (2015)
Dengue fever, a disease caused by dengue virus brought by a mosquito called Aedes aegypty, is one of the deadly diseases in Indonesia. To cope with it, natural pesticide can be used, which is boiled water of jatropha multifida's stem and Phaleria macrocarpa fruit pulp. It can be used to kill Aedes aegepty's larvae since those plants contain saponin compound. This research aims to identify the effectiveness of the extract of Jatropha multifida's stem and Phaleria macrocarpa fruit pulp boiled water in eradicating Aedes aegepty's larvae based on LC50. This research employs experimental method by using Completely Randomized Design (CDR) with two factors: (1) the concentrate of boiled water extract (P1=25%, P2=50%, P3=75%, P4=100%) and (2) the kinds of plant (E1= Jatorpha multifida's stem; E2= Phaleria macrocarpa fruit pulp) and with four repetitions. The result of the research shows that the extract of the boiled water of crown Phaleria macrocarpa fruit pulp whose LC50 is 64.68% is more effective in eradicating Aedes aegepty's larvae compared to the extract of the boiled water of Jatropha multifida's stem whose LC50 is 90.36%. It means that the boiled ater's extract of Phaleria macrocarpa fruit pulp can eradicate Aedes aegepty's larvae with only 64.68% concentrate while the boiled water's extract of Jatropha multifida's stem needs 90.36% concentrate. It is caused by the amount of saponin compound contained.